Atlas of Differential Diagnosis MRI - Fan, Guoguang; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
Aiming to equip readers with the knowledge required for accurate and timely diagnosis, this book presents illustrative cases that address a broad spectrum of clinical problems, including frequent, uncommon and rare diseases of brain, head and neck, spine, musculoskeletal system, chest and abdomen. To make readers understand easily, tips in differential diagnosis are summarized in the table, accompanying with typical images and key teaching points. It will be a valuable resource for diagnostic radiologists, residents, fellows, and related clinical doctors.
Characteristic of Brain MRI -- Brain Diseases -- Cerebrovascular and Infectious Diseases -- Ventricular and Cerebral Cistern Diseases -- Meningeal and Skull Diseases -- Skull Base Disease -- Eyelid and Eye Diseases -- Ear Diseases -- Paranasal Sinus and Nasal Cavity Disease -- Laryngeal Disease -- Spine Diseases -- Spinal Cord Diseases -- Bone and Bone Marrow Disease -- Joint and Soft Tissue Disease -- Respiratory Diseases -- Cardiac Vascular Diseases -- Benign and Malignant Breast Tumor -- Digestive Diseases -- Urinary System Diseases -- Reproductive System Diseases.
Keywords: Radiology; Radiology; Acquired Immunodeficiency Syndrome -- complications; Acquired Immunodeficiency Syndrome -- diagnostic imaging; Radiography; Diagnosis, Differential; Atlases